Land use and Geographical Planning towards National Solidarity - Akhbari, Mohamad (International Journal of Bio-resource and Stress Management, 2010)
The objective is know the influence of such geographical changes in Iran, also to understand the development. It is an important because of ethnic diversity and scattered population growth in the country influenced by geopolitics. Ethnic conflict has increased considerably in recent times and more interestingly, 72% of 120 major global conflicts is on ethnic issues. In the formation of political movement, people must know and understand the task or role of the governments, what policies and performance, who has been elected by the people to achieve the goals. Representatives of central part of the country mainly rule the Iranian government is due to spatial structure and geopolitical location, is always superior in power in compared with peripheral units.